Physiological and biochemical mechanisms of plants resistance to oxidative stress under peptide elicitor AtPep1 - Filiptsova, Halina G.; Yurin, Vladimir M. (Experimental Biology and Biotechnology, 2021)
The effect of the peptide elicitor AtPep1 on the resistance of soybean and pea plants to oxidative stress was studied. The concentration of the peptide 10– 9 mol/L has the maximum elicitor effect on these plants. It was shown that treatment of the aerial part of seedlings with this peptide leads to an increase in the activity of peroxidase and superoxide dismutase and a decrease in the level of lipid peroxidation products in plants under oxidative stress. Revealed effects cause an increase in the plants resistance to stress.
Keywords: peptide elicitor AtPep1; oxidative stress; reactive oxygen species; lipid peroxidation; peroxidase; superoxide dismutase